Peran Pelatihan Berbasis Kompetensi dalam Meningkatkan Produktivitas Tenaga Pendidik di Era Digital - Dinda Putri; Khalisatun Husna; Muhammad Arby Fahrezi; Tengku Darmansah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of digital technologies has changed the educational landscape, requiring educators to upgrade their skills to remain relevant and effective. Competency-based training is important in this context because of its focus on developing practical skills that can be directly applied in teaching. This paper discusses the role of competency-based training in improving educators’ productivity in the digital era. The method used is a literature study, which includes analysing various studies and articles related to this topic. The findings show that competency-based training acts as: 1) Skills Development; 2) Teaching Quality Improvement; and 3) Evaluation of Teaching Effectiveness. The purpose of this study is to provide insights into the importance of competency-based training in improving the productivity and teaching quality of educators in the digital era, and to encourage wider and more sustainable implementation of training.